Islam and its relate to violence - اىٍدرس اىٍصاغد نارزان فلٖ خي٘و (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
One of the greatest rules of religion that the prophet of mercy Muhammad has brought is that conversion to Islam is up to the personal conviction of individuals, and that the call to him is based on good wisdom and exhortation, not coercion and force. One of the things that Islam came to achieve is the treatment of everyone Of Muslims, and encourages them to peace, tolerance and non-violence. Sharia law has arranged to deal with peace among members of society in every part of the world, regardless of whether it is Muslim or otherwise. Because of what plagued the Islamic nation today the issue of violence, which described Islam, and there is no doubt that the violence is far from the religion of Islam, but an old phenomenon, and the detection of the roots of violence of contemporary places because Muslims today are facing many problems and challenges of the times. The phenomenon of the spread of violence is one of the problems of the age and the phenomenon of the most complex and dangerous to individuals and society The danger of this phenomenon in that it affects the relationship and the link between individuals in societies, and this phenomenon is increasing rapidly, and this affects the present of these societies and dark darkness on the future, and affect the future And the reputation of Islam today is exposed to the most virulent campaigns and the mere mention of the word terrorism or violence in some quarters is portrayed as an Islamic origin and action, but it is necessary in this age and the critical phase itself which is filled with ideas that attract individuals to violence and distance from peace and Tolerance needs a light to reveal the reality of the religion of Islam and its tolerance, peace and non-violence, and that the phenomenon of violence needs to confront the work and effective dialogue, as can not be the Islamic approach to peace, non-violence and tolerance, it is not appropriate to address the phenomenon of violence without considering its causes And its causes, and treatment of preventive and therapeutic methods and that the violence did not come arbitrarily and did not arise arbitrarily, but has its causes and causes, and know the cause is very important because the reason why determine the type of treatment prescription medicine, there is no treatment only after diagnosis, To address the concept of The same, its causes and treatment of preventive and curative means from an Islamic perspective.